Hypoxia Tolerance Declines with Age in the Absence of Methionine Sulfoxide Reductase (MSR) in Drosophila melanogaster - Nirthieca Suthakaran; Sanjana Chandran; Michael Iacobelli; David Binninger (MDPI AG, 2021)
Unlike the mammalian brain, Drosophila melanogaster can tolerate several hours of hypoxia without any tissue injury by entering a protective coma known as spreading depression. However, when oxygen is reintroduced, there is an increased production of reactive oxygen species (ROS) that causes oxidative damage. Methionine sulfoxide reductase (MSR) acts to restore functionality to oxidized methionine residues. In the present study, we have characterized in vivo effects of MSR deficiency on hypoxia tolerance throughout the lifespan of Drosophila. Flies subjected to sudden hypoxia that lacked MSR activity exhibited a longer recovery time and a reduced ability to survive hypoxic/re-oxygenation stress as they approached senescence. However, when hypoxia was induced slowly, MSR deficient flies recovered significantly quicker throughout their entire adult lifespan. In addition, the wildtype and MSR deficient flies had nearly 100% survival rates throughout their lifespan. Neuroprotective signaling mediated by decreased apoptotic pathway activation, as well as gene reprogramming and metabolic downregulation are possible reasons for why MSR deficient flies have faster recovery time and a higher survival rate upon slow induction of spreading depression. Our data are the first to suggest important roles of MSR and longevity pathways in hypoxia tolerance exhibited by Drosophila.